2006
DOI: 10.1038/sj.jhh.1002100
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nifedipine on adiponectin in hypertensive patients with type 2 diabetes mellitus

Abstract: Nifedipine, a dihydropyridine calcium antagonist, improves endothelial function in patients with hypercholesterolaemia by enhancing nitric oxide (NO) activity, and increases endothelial NO bioavailability by antioxidant mechanisms. We administered a long-acting nifedipine formulation (controlled release (CR) nifedipine: 20 mg/day) to hypertensive patients for 6 months. There were no other changes of drug treatment during therapy with CR nifedipine. Clinical and biochemical data obtained before and after CR nif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 46 publications
(54 reference statements)
1
47
0
Order By: Relevance
“…Some CCBs have also been reported to have the ability to increase adiponectin levels through the inhibition of reactive oxygen species generation 30 and of monocyte and platelet activation. 27 On the basis of these reports, we speculated that the blockade of RAS and of the calcium channel may be a powerful tool not only in patients with hypertension and pre-hemodialysis CKD, but also in hemodialysis patients for improving metabolic disturbance. In contrast, some studies have reported that statins increased circulating levels of adiponectin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some CCBs have also been reported to have the ability to increase adiponectin levels through the inhibition of reactive oxygen species generation 30 and of monocyte and platelet activation. 27 On the basis of these reports, we speculated that the blockade of RAS and of the calcium channel may be a powerful tool not only in patients with hypertension and pre-hemodialysis CKD, but also in hemodialysis patients for improving metabolic disturbance. In contrast, some studies have reported that statins increased circulating levels of adiponectin.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al 20 also investigated the effect of the RAS blockade and did not find any effect on adiponectin levels. However, several investigators reported that angiotensin-converting enzyme inhibitor, angiotensin II receptor blocker 25,26 and CCB 27 increase adiponectin levels in non-hemodialysis patients. Thus, we speculated that these drugs might also increase adiponectin levels in hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of the Journal of Human Hypertension, Nomura et al 18 extend these observations further by examining the effect of a calcium channel blocker (CCB), nifedipine on adiponectin concentrations in hypertensive patients with type II diabetes mellitus. Their study involved 103 subjects (73 hypertensives and 30 normotensive controls).…”
Section: Antihypertensive Treatment Adiponectin and Cardiovascular Rmentioning
confidence: 97%
“…The findings of Nomura et al 18 suggest a cardioprotective role (at least from the adiponectin perspective) of the CCB nifedipine, although it remains to be determined whether this is a nifedipine-specific effect or whether it is a class effect of all dihydropyridine calcium antagonists. The implication here is that CCBs, particularly nifedipine, may have beneficial effects on the cardiovascular system, with antiatherosclerotic effects beyond blood pressure lowering.…”
Section: Antihypertensive Treatment Adiponectin and Cardiovascular Rmentioning
confidence: 99%
“…In contrast, the main source of CD36 + -MVs in non-T2DM individuals is endothelial cells [12] . In addition, the blood levels of platelet-derived MVs and monocyte-derived MVs have been associated with diabetic microvascular damage [13][14][15][16] . However, elevated blood levels of endothelial-derived MVs have been suggested to predict the presence of coronary atherosclerotic lesions [17,18] .…”
Section: General Characteristics Of Mvsmentioning
confidence: 99%